A low-cost remote driver sleep monitoring system - FEYZİOĞLU, AHMET; ÇELEBİ, MEHMET FATİH (My University, 2022)
Today, the use of smart transportation systems has become widespread due to the change in the structure of cities, technological developments, and the increase in the number of vehicles. It aims at targets such as reducing the damage to people and the environment by increasing traffic safety with smart transportation systems. In addition, one of the big problems of long-distance drivers is falling asleep while driving. This is an event that puts both the driver’s life, the passengers in the vehicle, and the vehicles on the road in danger, and puts the company in a difficult situation if it works for a company. In this direction, the driver sleep alarm project has been developed. This project is a control system based on monitoring the user, measuring, and analyzing their movements. Literature research, which is the first stage of the project, was conducted and research continued throughout the project process. Within the scope of this project, a headset was designed for the driver’s sleep alarm and a mobile application was created. The first prototype of the project was built. First, in the project, the angle values made by the driver\"s head were produced with the IMU connected to the microcontroller. 10° to 20° margins identified as sleeping state for roll, pitch, and yaw angles. Later, a wearable headset was designed for the driver. Based on these angles produced in the microcontroller, an algorithm has been created that detects whether the driver is asleep. These generated angle values and status information were transferred from the headset to the mobile application via Bluetooth. This data transferred in the mobile application is reflected on the screen. In addition, an algorithm has been created in the mobile application, which sends a notification to the driver when sleep status is detected and sends an informative SMS to the headquarters if the driver is unresponsive to this notification. For the second prototype, it was aimed to produce a PCB for the headset and thus make a new mechanical design. Data mining applications are planned with the collected data from drivers for future works.
Keywords: Haberleşmeli Kontrol Sistemleri; İnsan ve Robot Etkileşimi; Donanım; Mikroprogramlama ve Kontrol Yapısı; Tümleşik Devreler; Elektronik Devreler; Bilgisayar Destekli Tasarım ve İmalat; Communication Control Systems; Human and Robot Interaction; Equipment; Microprogramming and Control Structure; Integrated Circuits; Electronic Circuits; Computer Aided Design and Manufacturing; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, DONANIM VE MİMARLIK; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, HARDWARE & ARCHITECTURE; ENGINEERING, MECHANICAL; ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING, MULTIDISCIPLINARY; Kontrol ve Optimizasyon; Medya Teknolojisi; Makine Mühendisliği; Elektrik ve Elektronik Mühendisliği; Kontrol ve Sistem Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Sinyal İşleme; Donanım ve Mimari; Fizik Bilimleri; Control and Optimization; Media Technology; Mechanical Engineering; Electrical and Electronic Engineering; Control and Systems Engineering; Computational Mechanics; Automotive Engineering; Signal Processing; Hardware and Architecture; Physical Sciences